Pendekatan Pembelajaran Mendalam sebagai Upaya Peningkatan Keterampilan Menulis Kreatif - Anita Candra Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Creative writing is a crucial skill that students must master, especially in elementary and secondary education. However, creative writing skills are often low due to conventional learning approaches that do not motivate students to think critically and reflectively. Deep learning is an approach that emphasizes in-depth conceptual understanding, critical reflection, and the development of creative thinking skills. This article aims to review the literature related to the implementation of deep learning in improving creative writing skills. The method used was a literature review, which searched for articles, journals, and books from current academic databases that discussed the relationship between deep learning and creative writing. The review results indicate that implementing deep learning through strategies such as reflective discussions, creative assignments, and connecting personal experiences with written materials can improve the quality of students' ideas, structure, and creative expression. Furthermore, the integration of technology, such as digital learning platforms and interactive media, also supports the effectiveness of deep learning in the context of creative writing. This article concludes that the deep learning approach not only improves technical writing skills but also fosters students' creativity, critical thinking, and intrinsic motivation. The implications of this research can serve as a basis for educators to design more effective and innovative writing learning strategies.